Continuous to Use Health and Fitness Applications: Extended TCT Models - Assyfa Meilyandra Panca Putri; Tengku Ezni Balqiah (UNIVED Press, 2026)
The rapid advancement of digital technology and high mobile penetration have driven the growth of health and fitness application usage. However, despite rising downloads, user retention remains low. This study investigates factors influencing continuance intention using the technology continuance theory (TCT). A quantitative approach was employed by distributing online questionnaires to 271 respondents, analyzed using pls-sem. Results show all hypotheses are supported, indicating the model’s effectiveness. This study contributes theoretically by extending TCT with lifestyle compatibility and perceived security, offering insights for developers to enhance user retention strategies.